2022
DOI: 10.1186/s12891-022-05396-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 attenuates diabetes-associated osteoporosis in ZDF rat, possibly through the RAGE pathway

Abstract: Background Diabetes-associated osteoporosis are partly caused by accumulation of advanced glycation endproducts (AGEs). Glucagon-like peptide-1 (GLP-1) has been shown to regulate bone turnover. Here we explore whether GLP-1 receptor agonist (GLP1RA) can have a beneficial effect on bone in diabetes by ameliorating AGEs. Methods In the present study, we evaluated the effects of the GLP-1 receptor agonist liraglutide, insulin and dipeptidyl peptidase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The hypoglycemic mechanism of Sax is to inhibit dipeptidyl dipeptidase‐4 (DPP‐4), thereby elevate the activity of glucagon‐like peptide 1 (GLP‐1) and glucose‐dependent intestinal insulin‐releasing peptide (GIP) (Bogdanov et al., 2022; Cheng et al., 2022). However, there are more and more reports on adverse reactions of heart failure relating to Sax (Benjamin et al., 2014; Edoardo et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypoglycemic mechanism of Sax is to inhibit dipeptidyl dipeptidase‐4 (DPP‐4), thereby elevate the activity of glucagon‐like peptide 1 (GLP‐1) and glucose‐dependent intestinal insulin‐releasing peptide (GIP) (Bogdanov et al., 2022; Cheng et al., 2022). However, there are more and more reports on adverse reactions of heart failure relating to Sax (Benjamin et al., 2014; Edoardo et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this study the influence of GQD on pharmacokinetics was investigated by the changes of the pharmacokinetic parameters of Sax. Furthermore, the assessment of the impact of GQD on the The hypoglycemic mechanism of Sax is to inhibit dipeptidyl dipeptidase-4 (DPP-4), thereby elevate the activity of glucagon-like peptide 1 (GLP-1) and glucose-dependent intestinal insulinreleasing peptide (GIP) (Bogdanov et al, 2022;Cheng et al, 2022).…”
Section: Effect On Liver Injurymentioning
confidence: 99%
“…An animal study on rats showed that liraglutide improved bone remodeling parameters by increasing the bone formation marker osteocalcin and the activity of alkaline phosphatase (ALP) while decreasing CTX (a bone resorption marker) with no change in P1NP (another bone formation marker). ( 49 ) In ovariectomized mice, both liraglutide and a quinoxaline‐based compound prevented bone loss, as evidenced by increased P1NP and decreased CTX levels, indicating enhanced bone formation and reduced bone resorption. However, these effects were observed only with exenatide treatment, not with liraglutide.…”
Section: Effects Of Incretins On Bone Healthmentioning
confidence: 95%
“…Overall, animal studies suggest that GLP-1 RAs, particularly exenatide (53)(54)(55)(56)(57)61,63,64) and liraglutide, (46,(49)(50)(51)65) may have beneficial effects on bone health by promoting bone formation, improving bone microarchitecture, and potentially preventing bone loss. However, the effects on bone strength are less consistent and may depend on the specific GLP-1 RA used and the study conditions.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation